Rare Case of OHVIRA with Ectopic Inguinal Hemiuterus and Ovary - Welke, Stefanie; Kosch, Ferdinand; Müller, Andreas; Hufnagel-Schmude, Amelie; Rother, Leonie; Ellerkamp, Verena (European Journal of Pediatric Surgery Reports, 2025)
A 12-year-old girl presented with inguinal swelling and recurrent groin pain since menarche. Ultrasound showed an inguinally located ovary with normal perfusion. Herniorrhaphy revealed an ectopic inguinal left ovary with fallopian tube and atretic hemiuterus and a closed internal inguinal ring. Laparoscopy revealed a right-sided hemiuterus and vaginally palpable cervix, leading to the diagnosis of ectopic OHVIRA syndrome type 1.2. The left hemiuterus was resected and the left ovary was pulled through the inguinal canal into the abdomen. During 12 months of follow-up, the left ovary showed normal perfusion and sonomorphologic appearance, menstrual periods were uneventful.
Keywords: OHVIRA syndrome; hemiuterus; hemivagina; vaginal obstruction